Biosynthesis, Antibacterial Activity, The Photocatalytic Performance of ZNO NPS by use of Leaf Extract of the Plant Primo Fiore - Karrar Hazim, Zahraa F Khudair, Iman K. Kadhim, Lidia Mohamed, Ghusoon Faidhi Hameed, Faris J. Alyasiri (Pakistan Journal of Medical & Health Sciences, 2022)
The leaf extract of the plant Primo Fiore was used in this study to synthesize environmentally-friendly nanotechnologies. This eco-friendly method is non-toxic and does not hurt the environment. The approach is cost-effective, simple to use, and extremely efficient, with the ability to adjust the properties of the resultant compounds. For example, the ZnO compound can be controlled using the same plant extract and reaction. The impact of calcination temperature on the physical properties of ZnO NPs has been studied. X-ray diffraction (XRD) and energy dispersive spectroscopy were used to determine the structural and chemical composition of ZnO NPs (EDX). Field emission scanning electron microscopy (FESEM) and transmission electron microscopy were used to examine the morphological features of produced nanoparticles (TEM). The existence of functional groups was investigated using Fourier transform infrared spectroscopy (FTIR), according to the FESEM pictures. Most of the nanoparticles are on the nanoscale. This study demonstrated the efficacy of zinc oxide in the treatment of wastewater pollution for the degradation of colors in organic contaminants in the water medium, destroying the dye rhodamine B and its antibacterial properties. Zinc oxide nanoparticles (ZnO-NP) have been demonstrated to have a good antibacterial capability against both gram-positive and gram-negative bacteria in this study, to investigate the antibacterial activity of zinc oxide nanoparticles.